Empowerment of Bongo Religious Tourism Village, Gorontalo Province Through Digital Marketing Strategy - Gobel, Yulia Puspitasari (Amalee: Indonesian Journal of Community Research and Engagement, 2023)
The Bongo Religious tourism village destination is a tourist village that has a beautifully natural feel with a culture that is thick with Islamic values, Bongo Village has 208 MSMEs. With the number of MSME actors marketing the products produced and with not being socialized to people who are outside the province of Gorontalo even though the Bubohu Bongo Religious Tourism Village came out as the second winner of ADWI 2021, because the publication of the religious tourism village has not spread widely. Therefore the solutions for MSME problems and publication of religious tourism villages are 1) Stimulating the public and government to be active in supporting MSME products and religious tourism destinations, 2) Optimizing Online Marketing as an attraction for domestic and foreign tourists, 3) creating and managing online marketing media, 6) implemented continuously. Implementation of activities Implementation of community service for Community Empowerment of UMKM Actors and Publication of destinations in the Bongo Religious Tourism village with an Online Marketing approach, carried out through workshop activities on August 1, 20,22 at Dulanga Beach, Bongo Village. Training and mentoring are carried out to increase public awareness of the use of social media as online marketing in increasing MSME businesses and publishing bongo religious tourism destinations. This is shown by the existence of a religious tourism website that markets typical bongo village products.